2016
DOI: 10.15406/bbij.2016.03.00055
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Snowball Sampling and Sequential Sampling Technique

Abstract: The article provides the description and comparison of two non-random samplings which are snowball or chain referral sampling and sequential sampling. Snowball sampling has been widely used in qualitative sociological research, especially in the study of deviant behavior and is used in the place where the population is hard to reach. It also described different form of sampling method. While in sequential sampling, sampling was taken at a given time interval and modification can be made by correcting the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
237
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(256 citation statements)
references
References 6 publications
0
237
0
19
Order By: Relevance
“…Basing on assumption means one will generate inappropriate generalization of the population [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Basing on assumption means one will generate inappropriate generalization of the population [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst this strategy enhanced successful recruitment in their study, it appeared to have contributed to the selection bias observed in the study leading to a homogenous sample of Jamaican men (Nanton & Dale, ). The risk of selection bias often associated with snowball sampling was minimised in this study by complementing it with additional recruitment strategies (Etikan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Snowball sampling thrives on the use of personal relationship networks to access participants who otherwise may not have been aware of, or participated in a study (Etikan, Alkassim, & Abubakar, 2016;Wohl et al, 2017). Although prone to selection bias which may result from over-representation of members of a particular participant's network (Etikan et al, 2016), snowball sampling has been widely acknowledged as useful in promoting research participation among "hard to reach" populations in a costeffective and timely manner (Richards & Morse, 2007;Sadler, Lee, Lim, & Fullerton, 2011;Wohl et al, 2017). Nanton and Dale (2011) successfully used snowball sampling to recruit African-Caribbean men with CaP (n = 16) into their qualitative study.…”
Section: Snowball Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The snowball sampling method is applied to recruit a purposive sample (i.e. stakeholders thought to be most important to the issue under study), whereby the researcher asks respondents to identify other stakeholders the researcher may contanct (Etikan et al 2016).…”
Section: Stakeholder Identificationmentioning
confidence: 99%